Hubungan Gaya Kepemimpinan dan Kompensasi terhadap Kepuasan Kerja dan Kinerja Karyawan pada PT Bank Riau Kepri Cabang Utama Pekanbaru - Hendriani, Susi; Sari , Wella Mayang; Yovita, Indri (Jurnal Aplikasi Manajemen, 2014)
This study aims to find out the correlation between leadership style and Compensation towards Job Satisfaction and Staff working Performance in Riau Bank Ltd, Riau Archipelago. The research population were 110 Staffs of Riau Bank Main Unit Branch of Pekanbaru, Riau Archipelago. Research samples were 25 of the population, taken by probability, using Purposive Stratified Random Sampling technique. By this technique, the sample were taken based on certain degree of stratification or by reference, in order to obtain a representative sample. Data analysis was intended to find out the correlation between independent variable (x), namely leadership style and motivation and dependent variable (Y) i.e, job satisfaction and working performance of the staff of Riau Bank main branch Pekanbaru Riau, Riau Archipelago. Both analysis and interpretation used descriptive Analysis and verified methods. Descriptive analysis method was used to describe the characteristics of respondents and the research variable, whereas the verified method was used to test the research hypothesis using relevant statistic test. The verified method used in this study is the Path Analysis. The results of the research showed that there was a significant correlation between leadership style and job satisfaction. Thus, the hypothesis is accepted. Leadership style also had a significant influence on job performance of staff and there is a significant influence of the compensation on leadership style in Riau Bank Main Branch Pekanbaru, Riau Archipelago.